Rifamycin congeners kanglemycins are active against rifampicin-resistant bacteria via a distinct mechanism. Issue 1 (December 2018) - Peek, James; Lilic, Mirjana; Montiel, Daniel; Milshteyn, Aleksandr; Woodworth, Ian; Biggins, John; Ternei, Melinda; Calle, Paula; Danziger, Michael; Warrier, Thulasi; Saito, Kohta; Braffman, Nathaniel; et al.
Abstract Rifamycin antibiotics (Rifs) target bacterial RNA polymerases (RNAPs) and are widely used to treat infections including tuberculosis. The utility of these compounds is threatened by the increasing incidence of resistance (RifR ). As resistance mechanisms found in clinical settings may also occur in natural environments, here we postulated that bacteria could have evolved to produce rifamycin congeners active against clinically relevant resistance phenotypes. We survey soil metagenomes and identify a tailoring enzyme-rich family of gene clusters encoding biosynthesis of rifamycin congeners (kanglemycins, Kangs) with potent in vivo and in vitro activity against the most common clinically relevant RifR mutations. Our structural and mechanistic analyses reveal the basis for Kang inhibition of RifR RNAP. Unlike Rifs, Kangs function through a mechanism that includes interfering with 5′-initiating substrate binding. Our results suggest that examining soil microbiomes for new analogues of clinically used antibiotics may uncover metabolites capable of circumventing clinically important resistance mechanisms. Resistance to rifamycin antibiotics, which target bacterial RNA polymerases, is a growing problem. Here, the authors identify gene clusters from soil metagenomes encoding production of rifamycin analogues that are active against rifampicin-resistant bacteria through a distinct mechanism.